Blood Ties and Fictive Ties : Adoption and Family Life in Early Modern France - Gager, Kristin Elizabeth (Book collections on Project MUSE., 2014)
In Paris during the sixteenth and seventeenth centuries, the practice of adopting children was strongly discouraged by cultural, religious, and legal authorities on the grounds that it disrupted family blood lines. In fact, historians have assumed that adoption had generally not been practiced in France or in the rest of Europe since late antiquity. Challenging this view, Kristin Gager brings to light evidence showing how married couples and single men and women from the artisan neighborhoods in early modern Paris did manage to adopt children as their legal heirs. In so doing, she offers a.